Heroes of the Holocaust - Gottfried, Ted.; Alcorn, Stephen (Brookfield, Conn. : Twenty-First Century Books, 2001)
Describes resistance to the Holocaust in Nazi-occupied Europe.
Includes bibliographical references (p. 109-110) and index.
Wilson's Senior High School, November 2002
Booklist, May 2001
Voice of Youth Advocates (V.O.Y.A.), April 2002
Young Adult
Keywords: World War, 1939-1945 -- Jews -- Rescue; Righteous Gentiles in the Holocaust; Holocaust, 1933-1945.